The effect of nano-γAl2O3 additive on early hydration of calcium aluminate cement. (15th January 2018) - Chen, Junhong; Liang, Chaojing; Li, Bin; Wang, Enhui; Li, Guangqi; Hou, Xinmei
Highlights: The early-age hydration heat of cement was increased with nano-γAl2 O3 introduction. Nano-γAl2 O3 additive could promote the formation of the amount of main hydrates. Nano-γAl2 O3 additive contributed to the denser microstructure of CAC. Abstract: Aiming to solve the decrease of the mechanical strength of calcium aluminate cement (CAC) at high temperature, nano-γAl2 O3 additive ranging from 0.5 to 1.5 mass% was added in CAC with water to cement ratio (w/c) of 0.36 respectively. The influence of nano-γAl2 O3 additive on hydration heat was studied by isothermal calorimetry. It shows that nano-γAl2 O3 additive increases heat release rate and shortens the induction period of hydration. X-ray diffraction (XRD) and thermal analysis (TG-DTA) demonstrate that the main hydrate products are CaAl2 O4 ·10H2 O (CAH10 ) and Ca2 Al2 O6 ·8H2 O (C2 AH8 ) and their amounts increase obviously with nano-γAl2 O3 additive. Besides these, no other new phases are formed. The microstructure development of the hydrates was characterized by scanning electron microscopy (SEM). Due to the formation of smaller hydrate crystals together with amorphous aluminum gel, the microstructure of CAC with 1 mass% nano-γAl2 O3 additive becomes much denser, which contributes to enhance the mechanical strength at high temperature during the CAC hardening process.